The role of the nobility in the creation of Gallo-Frankish society in the late fifth and sixth centuries AD - Wood, Catrin Mair Lewis (2002)
The aim of this dissertation is to explore the contribution made by the nobility, both Gallo-Roman and Frankish, to the creation of a new society after the collapse of imperial authority in the west, Gallo-Frankish society.